Assessing User Satisfaction in E-Haj Systems: Insights from Bangladesh - Alam, S. M. Ashraful; Islam, Md. Tariqul; Akter, Most. Sadia; Islam, Md. Kamrul; Bhuiyan, Mohammad Rakibul Islam (Journal of Information Systems and Informatics, 2024)
This study examines how e-haj management systems in Bangladesh affect user satisfaction. Therefore, the authors presented the hypothesis using webQual 4.0 Model. Data was collected using a 5-point-lickert questionnaire. 347 valid data were collected from Dhaka city. SPSS 27 displayed descriptive statistics, and Smart PLS 3.3.3 was analysed for measurement and structural model. The study found the positive impact of the usability, information quality, and service information quality of e-hajj on users’ satisfaction. Thus, e-government implementers can get benefits from the findings of the paper as they come to know what factors motivates individuals to use the government’s e-haj management portal. This finding also suggested that government should focus on website’s easy to navigate option, updated information and 24/7 customer service. As a result, this tendency of the citizens towards e-government services will be increased day by day and motivated to accept these e-hajj system. This research will increase trust and improve the democratic process for all citizens including businesses, or different government agencies by enhancing service quality provided to them. Small sample size, data collection period, and location are the limitations of this study. Future researchers may combine more model’s items and reduce these limitations to improve practical application studies.